FindMyApps compared with usual tablet use to promote social health of community-dwelling people with mild dementia and their informal caregivers: a randomised controlled trialResearch in context - David P. Neal; Teake P. Ettema; Marissa D. Zwan; Karin Dijkstra; Evelyn Finnema; Maud Graff; Majon Muller; Rose-Marie Dröes (EClinicalMedicine, 2023)
Summary: Background: FindMyApps is a tablet-based eHealth intervention designed to help people learn to use a tablet and find easy-to-use apps. This study evaluated the effectiveness of FindMyApps for supporting social health of people living with dementia, and sense of competence of their informal caregivers. Methods: A single-centre, two-arm, non-blinded randomised controlled trial was conducted (Netherlands Trial Register NL8157). From 1st January 2020 to 31st July 2022, community-dwelling people in the Netherlands with a pre-established diagnosis of mild cognitive impairment (MCI) or dementia (Brief Cognitive Rating Scale 17–32), an informal caregiver and internet connection were allocated by block randomisation to receive FindMyApps or digital care-as-usual. Primary outcomes (measured at baseline and after three months) for people with dementia/MCI were self-management (Adult Social Care Outcomes Toolkit total score) and social participation (Maastricht Social Participation Profile frequency and diversity scores), and for caregivers, sense of competence (Short Sense of Competence Questionnaire total score). Between-group differences were tested by MANCOVA or ANCOVA (alpha = 0.05). Findings: 150 dyads were randomised (FindMyApps n = 76, care-as-usual n = 74). Follow-up data were available for 128 dyads (FindMyApps n = 64, care-as-usual n = 64), who were included in the analysis in the trial arm to which they were assigned. No harms of the intervention were identified. There were no statistically significant differences in outcomes for people with dementia/MCI at group level. Diagnosis and experiencing apathy appeared to be relevant effect modifiers of secondary outcomes (neuropsychiatric symptoms, positive affect, sense of belonging, and pleasurable activities). Caregivers who received FindMyApps had higher sense of competence at three months (F [1,123] = 7.01, p = 0.0092, η2 = 0.054). Interpretation: Overall we found no evidence that the FindMyApps intervention better supported social participation or self-management of people with MCI/dementia than digital care-as-usual. FindMyApps does seem to better support informal caregivers’ sense of competence. For people with a diagnosis of mild dementia and older people, better tailored interventions, implementation and outcome measures may be needed. Funding: Marie Skłodowska Curie Actions Innovative Training Network H2020 MSCA ITN, grant agreement number 813196.